Enzymatic activities of circulating plasma proteasomes in newly diagnosed multiple myeloma patients treated with carfilzomib, lenalidomide and dexamethasone. Issue 3 (4th March 2017) - Manasanch, Elisabet E.; de Larrea, Carlos Fernández; Zingone, Adriana; Steinberg, Seth M.; Kwok, Mary; Tageja, Nishant; Bhutani, Manisha; Kazandjian, Dickran; Roschewski, Mark; Wu, Peter; Carter, George; Zuchlinski, Diamond; et al.
Abstract: The proteasome inhibitor carfilzomib is highly effective in the treatment of multiple myeloma. It irreversibly binds the chymotrypsin-like active site in the β5 subunit of the 20S proteasome. Despite impressive response rates when carfilzomib is used in combination with immunomodulatory agents in newly diagnosed multiple myeloma patients; no biomarker exists to accurately predict response and clinical outcomes. We prospectively assessed the activity in peripheral blood of the chymotrypsin-like (CHYM), caspase-like (CASP) and trypsin-like (TRYP) proteolytic sites in 45 newly diagnosed multiple myeloma patients treated with eight cycles of carfilzomib, lenalidomide and dexamethasone (CRd) (NCT01402284). Samples were collected per protocol and proteasome activity measured through a fluorogenic assay. Median CHYM levels after one dose of carfilzomib decreased by >70%. CHYM and CASP activity decreased throughout treatment reaching a minimum after eight cycles of treatment. Higher levels of proteasome activity associated with higher disease burden ( r > 0.30; p < 0.05) and higher disease stage (0.10 < p <0.20). No association was found with the probability of achieving a complete response, minimal residual disease negativity or time to best response. Further studies evaluating proteasome activity in malignant plasma cells may help elucidate how proteasome activity can be used as a biomarker in multiple myeloma.